THE ROLE OF BLOCKCHAIN AS DIGITAL INFRASTRUCTURE IN SHARIA-BASED MSME FINANCING - Hasan, Hurriah Ali (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This research aims to analyze the role of blockchain as a digital infrastructure to support sharia-based MSME financing in Indonesia. The focus of the research is directed at how blockchain can improve the transparency, accountability, and effectiveness of sharia contract processes such as murabahah, mudharabah, musyarakah, and qardhul hasan. The research uses an exploratory qualitative approach through semi-structured interviews with sharia MSME actors, sharia microfinance institutions (BMT and sharia cooperatives), blockchain technology providers, and sharia regulators. The data is strengthened through observation of the financing process and contract documentation. Data analysis was carried out using thematic coding techniques and source triangulation. The results of the study show that blockchain provides an immutable, transparent, and real-time transaction recording system so that it can improve the verification and monitoring process of sharia compliance. Blockchain enables the automation of margin calculation and profit sharing through smart contracts, reduces the risk of asymmetric information, and helps build a digital track record of MSMEs as the basis for assessing financing eligibility. However, the adoption of this technology is still hampered by low digital literacy, infrastructure readiness, and lack of sharia regulations related to new technologies. The implementation of blockchain can increase the effectiveness of sharia MSME financing, simplify sharia audits, reduce the administrative burden of financing institutions, and expand access to financing for MSMEs. The findings of this study provide guidance for BMTs, sharia cooperatives, and regulators to develop a digital financing model that is secure, transparent, and in accordance with sharia principles. This research offers an empirical understanding and conceptual model of blockchain as a digital infrastructure for sharia financing, a topic that is still very limited in the Indonesian literature. This study integrates the perspectives of MSME actors, financing institutions, technology providers, and regulators, resulting in a holistic analysis related to the readiness of the digital ecosystem for sharia-based MSME financing.